2000
DOI: 10.1016/s0378-1097(00)00258-5
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in membrane fatty acid profiles associated with acid adaptation of Streptococcus mutans

Abstract: Cells of Streptococcus mutans UA159 physiologically adapted to acidification during growth at pH 5 in glucose-limited chemostat cultures were enriched in mono-unsaturated and longer chain fatty acids compared with unadapted cells grown under the same conditions but at pH 7. Ratios of unsaturated to saturated fatty acids in the cells were, respectively, 1.2 and 0.3. Cyclopropane fatty acids were not detected. Streptococcus sobrinus 6715, which is known to have minimal acid-adaptive capacity, showed only minimal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
71
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(78 citation statements)
references
References 20 publications
(23 reference statements)
7
71
0
Order By: Relevance
“…S. mutans strains grown at pH 5 had increased levels of monounsaturated fatty acids and longerchain fatty acids than did those grown at pH 7. In contrast S. sobrinus 6715, which does not adapt well to pH stress, was less capable of changing its membrane composition (187). Acidadapted I. monocytogenes was also more tolerant to nisin and other ionophores than was the nonadapted counterpart (67).…”
Section: Cell Membrane Changesmentioning
confidence: 99%
“…S. mutans strains grown at pH 5 had increased levels of monounsaturated fatty acids and longerchain fatty acids than did those grown at pH 7. In contrast S. sobrinus 6715, which does not adapt well to pH stress, was less capable of changing its membrane composition (187). Acidadapted I. monocytogenes was also more tolerant to nisin and other ionophores than was the nonadapted counterpart (67).…”
Section: Cell Membrane Changesmentioning
confidence: 99%
“…Dental plaque forms through a sequential events resulting in a structurally and functionally organized species rich microbial community [6,101]. Once plaque forms, its species composition at a site is characterized by degree of stability among the component species.…”
Section: Progression Of Dental Biofilmmentioning
confidence: 99%
“…It has been established that the F-ATPase is transcriptionally up-regulated during growth at pH values below 7 (16,17). Recently, we have shown that the membrane fatty acid composition of S. mutans changes dramatically during growth at low pH values (7,8,28). In an effort to contribute to the characterization of additional factors involved with the acid adaptation process, we have looked to identify proteins that allow S. mutans to survive and grow in an acidified environment.…”
Section: Discussionmentioning
confidence: 99%